Implementation of veno-venous extracorporeal membrane oxygenation in a COVID-19 convalescent - Gawda, Ryszard; Marszalski, Maciej; Molsa, Maciej; Piwoda, Maciej; Pietka, Marek; Gawor, Maciej; Mielnicki, Wojciech; Dyla, Agnieszka; Czarnik, Tomasz (Anestezjologia Intensywna Terapia, 2020)
Dear Editor, We would like to present a case of successful implementation of veno-venous extracorporeal membrane oxygenation (ECMO) in a COVID-19 convalescent. Many experts suggest that during a pandemic ECMO should be applied in strictly defined cases for COVID-19 patients, mainly because of the resource-consuming nature of extracorporeal therapy [1, 2]. Current guidelines state that ECMO is contraindicated after seven days of mechanical ventilation, including in critically ill COVID-19 patients [3]. Extracorporeal treatment in our COVID-19 convalescent was launched at the late stage of severe acute respiratory distress syndrome (ARDS), which was also affected by the onset of septic shock. We believe that this is the first case of ECMO therapy in a COVID-19 convalescent to be described in the literature. Written informed consent from the patient was obtained to present this case.